2019
DOI: 10.1038/s41598-019-43594-9
|View full text |Cite
|
Sign up to set email alerts
|

Attempted Arm and Hand Movements can be Decoded from Low-Frequency EEG from Persons with Spinal Cord Injury

Abstract: We show that persons with spinal cord injury (SCI) retain decodable neural correlates of attempted arm and hand movements. We investigated hand open, palmar grasp, lateral grasp, pronation, and supination in 10 persons with cervical SCI. Discriminative movement information was provided by the time-domain of low-frequency electroencephalography (EEG) signals. Based on these signals, we obtained a maximum average classification accuracy of 45% (chance level was 20%) with respect to the five investigated classes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 87 publications
8
117
0
Order By: Relevance
“…Finally, although the task may no longer be strictly a pure mental command, there are contexts where some users may be asked to perform quasimovements (maximally reduced movements indistinguishable through ElectroMyoGraphy (EMG) measures [74]), which seems promising to gradually train users to perform motor imagery. In the context of neuroprostheses or stroke-rehabilitation applications, users suffering from motor impairments can also be asked to perform attempted movements instead of imagined movements [272]. However, it is uncertain how the recommendations reported in the present review apply to training non-mental tasks.…”
Section: Motor-imagery Tasksmentioning
confidence: 99%
“…Finally, although the task may no longer be strictly a pure mental command, there are contexts where some users may be asked to perform quasimovements (maximally reduced movements indistinguishable through ElectroMyoGraphy (EMG) measures [74]), which seems promising to gradually train users to perform motor imagery. In the context of neuroprostheses or stroke-rehabilitation applications, users suffering from motor impairments can also be asked to perform attempted movements instead of imagined movements [272]. However, it is uncertain how the recommendations reported in the present review apply to training non-mental tasks.…”
Section: Motor-imagery Tasksmentioning
confidence: 99%
“…Recent investigations have shown that brain patterns of singular upper limb movements can be identified and decoded from EEGs’ low frequency time domain (LFTD) signals. These so called movement-related cortical potentials (MRCPs) ( Shibasaki et al, 1980 ) have been shown to hold discriminable information of upper limb movements ( Ofner et al, 2017 ), different grasps ( Agashe et al, 2015 ; Jochumsen et al, 2016 ), different reach-and-grasp actions ( Randazzo et al, 2015 ; Iturrate et al, 2018 ; Schwarz et al, 2018 , 2019 ) and can even be decoded online ( Ofner et al, 2019 ; Schwarz et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from encoding the initiation of executed ( Lew et al., 2012 ), attempted ( Ofner et al., 2019 ) and imagined ( Pereira et al., 2018 ) upper-limb movements, MRCPs have also been reported to encode information about goal-directedness ( Pereira et al., 2017 ), speed ( Gu et al., 2009 ), force ( Jochumsen et al., 2013 ), grasp types ( Schwarz et al., 2018 ), other movements of the upper limb ( Ofner et al., 2017 , Ofner et al., 2019 ) and movement direction ( Li et al., 2012 , Waldert et al., 2008 ). The representation of directional information within the MRCP is typically studied during center-out reaching tasks and aligned to the response ( Robinson and Vinod, 2016 ).…”
Section: Introductionmentioning
confidence: 99%